2005
DOI: 10.1111/j.1551-2916.2005.00305.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Assessment of Plasticity of Nanocrystalline 1.7 mol% Yttria Tetragonal Zirconia Polycrystals

Abstract: High temperature mechanical behavior of nanocrystalline 1.7 mol% (3 wt%) yttria tetragonal zirconia polycrystals (nc‐YTZP) was characterized by compression creep tests. The hot isostatically pressed nc‐YTZP with mean grain size of 120 nm was subjected to grain growth to obtain grain sizes in the range of 120–310 nm. Direct measurements of the creep parameters were performed in the temperature range 1150°–1300°C and stress range 5–400 MPa. The strain rates at 1150°C ranged between 2 × 10−7 and 9 × 10−5 s−1 when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Gutierrez‐Mora et al . also reported activation energy values close to 700 kJ/mol in nanocrystalline Y‐TZP crept at temperatures between 1150°C and 1250°C, and stresses ranging between 5 and 200 MPa.…”
Section: Resultsmentioning
confidence: 88%
“…Gutierrez‐Mora et al . also reported activation energy values close to 700 kJ/mol in nanocrystalline Y‐TZP crept at temperatures between 1150°C and 1250°C, and stresses ranging between 5 and 200 MPa.…”
Section: Resultsmentioning
confidence: 88%
“…23 It is interesting to note that there have been other recent studies that have also revealed that the threshold stress approach is unable to rationalize the experimental observations in a 4 mol% yttria-stabilized tetragonal zirconia 35 as well as some nanocrystalline zirconias. 36 Although some studies have noted intragranular dislocations, 18 several other studies on superplastic zirconias have noted the lack of intragranular dislocations. 35,37 A recent study by Dominguez-Rodriguez et al 38 concluded that observation of intergranular dislocation in deformed 3YTZ samples were experimental artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…Improved creep resistance has been reported in 50-70 nm Y-TZP deformed at 1200uC, in agreement with model predictions. [58][59][60][61][62][63] In this regard, it has been shown that the effect of segregation becomes increasingly important as the grain size becomes smaller. Indirect experimental evidence for this is shown in Fig.…”
Section: Nature Of Grain Boundariesmentioning
confidence: 99%